Increased efficacy of a dose-dense regimen of neoadjuvant chemotherapy in breast carcinoma: a retrospective analysis - Melichar, Bohuslav; Hornychová, Helena; Kalábová, Hana; Bašová, Hana; Mergancová, Jindřiška; Urminská, Hana; Jandík, Pavel; Cervinka, Vladimír; Laco, Jan; Ryška, Aleš (Medical oncology (Northwood, London, England), 2012)
Neoadjuvant chemotherapy is being increasingly used in the treatment of breast carcinoma. We performed a single-center retrospective analysis of the results of neoadjuvant therapy in 376 breast carcinoma patients treated with three different regimens combining doxorubicin and paclitaxel (AT), dose-dense doxorubicin and cyclophosphamide with sequential weekly paclitaxel (DD AC-P), or the combination of trastuzumab with chemotherapy (DD AC-PT). The expression of estrogen receptors (ER), progesterone receptors (PR) and human epidermal growth factor receptor (HER)-2 was determined immunohistochemically. Pathological response was determined in 318 patients. Pathological complete response (pCR) was observed in 18% of patients. The pCR rate was significantly higher in patients treated with DD regimen (22 vs. 13%) and younger than 55 years (23 vs. 13%). The pCR rate was higher in patients with triple negative (TN) tumors (43%) and tumors over-expressing HER-2 (HER-2+; 28%) compared to patients with ER- or PR-positive tumors not expressing HER-2 (ER/PR+HER-2-; 6%). In patients with TN tumors pCR rate was significantly higher after treatment with DD AC-P compared to AT (61 vs. 22%, p=0.005). pCR was associated with significantly improved relapse-free survival (RFS) and overall survival (OS), but when analysis was performed based on tumor phenotype, the difference was significant only in patients with TN tumors. In multivariate analysis, pCR, stage, and ER expression were significant predictors of RFS, while pCR, stage, ER and DD regimen were significant predictors of OS. In conclusion, present data indicate superiority of a DD regimen in obtaining pCR in patients with breast carcinoma treated with neoadjuvant chemotherapy. The difference in efficacy is due mostly to markedly higher pCR rate in patients with TN tumors.
Keywords: lidé; Middle Aged; Adult; Female; retrospektivní studie; imunohistochemie; Breast Neoplasms; nádory prsu; Humans; neoadjuvantní terapie; protokoly protinádorové kombinované chemoterapie; Immunohistochemistry; receptor erbB-2; lidé středního věku; ženské pohlaví; Receptors, Estrogen; receptory pro estrogeny; receptory progesteronu; Aged; Receptors, Progesterone; Retrospective Studies; Neoadjuvant Therapy; Receptor, ErbB-2; dospělí; Antineoplastic Combined Chemotherapy Protocols; senioři